Modelling and Assessing the Performance of Hybrid PV-CSP Plants in Morocco: A Parametric Study - Loubna Bousselamti; Mohamed Cherkaoui (International Journal of Photoenergy)
Based on the examination of the efficiency of solar plants, this study focuses on three main plants: a photovoltaic (PV) plant, a concentrated solar power (CSP) plant, and a hybrid PV/CSP plant. The modelling of the three plants has been implemented to evaluate the influence of design parameters (orientation angles, solar multiple (SM), thermal energy storage capacity (TES), and fraction of hybridization) on them. Several simulations have been recreated and discussed in details to study the optimal configuration of the two first plants and the profitability of the PV/CSP plants for Ouarzazate (Morocco) location. The findings demonstrate that the optimal orientation angles and TES/SM, respectively, affect the performances of PV and CSP plants, and they also reveal that PV/CSP systems have the benefits to increase the annual energy produced, reduce the cost, and offer a high dispatchability to supply a baseload. The implementing of optimal PV/CSP plant has a great economic impact on Ouarzazate city.